2021
DOI: 10.3390/diagnostics11020265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of COVID-19 Pneumonia Lung Extension by Specific Software and Correlation with Patient Clinical Outcome

Abstract: Lung infection named as COVID-19 is an infectious disease caused by the most recently discovered coronavirus 2 (SARS-CoV-2). CT (computed tomography) has been shown to have good sensitivity in comparison with RT-PCR, particularly in early stages. However, CT findings appear to not always be related to a certain clinical severity. The aim of this study is to evaluate a correlation between the percentage of lung parenchyma volume involved with COVID-19 infection (compared to the total lung volume) at baseline di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Most COVID-19 patients experience similar symptoms, and the causes of death are related to low oxygen saturation and respiratory problems in the lungs. 13 Furthermore, from the analysis that has been carried out, in this study it was found that there was no relationship between the number of lymphocytes, the number of erythrocytes, the Hb level, the number of leukocytes, and the number of platelets on the degree of severity and outcome of pediatric cancer patients with COVID-19 infection. Research conducted in Wuhan, China showed no significant difference between an increase in the number of lymphocytes and the severity of pediatric patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Most COVID-19 patients experience similar symptoms, and the causes of death are related to low oxygen saturation and respiratory problems in the lungs. 13 Furthermore, from the analysis that has been carried out, in this study it was found that there was no relationship between the number of lymphocytes, the number of erythrocytes, the Hb level, the number of leukocytes, and the number of platelets on the degree of severity and outcome of pediatric cancer patients with COVID-19 infection. Research conducted in Wuhan, China showed no significant difference between an increase in the number of lymphocytes and the severity of pediatric patients.…”
Section: Discussionmentioning
confidence: 63%
“…12 Another study has shown a relationship between shortness of breath symptoms and the need for ventilators in patients. Annoni et al, 2021 stated in their research that COVID-19 patients with SpO2 <90% were associated with death outcomes. Patients with shortness of breath experience low oxygen saturation and need ventilation assistance, so it can be concluded that these two studies prove the association of symptoms of shortness of breath with the death of patients with COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…This quantitative approach enables an automated assessment of the pulmonary infection, depicting infection areas as high attenuation areas (HAAs) in respect of a defined threshold value ranging from 650 Hounsfield unit (HU) to 3071 HU. The amount of infected lung defined as the percentage of lung parenchyma above the predefined vendor-specific threshold of 650 HU (HAA%, HAA/total lung volume) was automatically calculated by the dedicated software for both lungs [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…High attenuation area (HAA) was defined as the quantified percentage of imaged lung volume with attenuation values between −600 and −250 Hounsfield units (HU), and low attenuation area (LAA) as <−950 HU ( 19 , 20 ). HAA corresponds to pneumonia-related alterations such as GGOs and consolidation ( 18 ). Airway measurements were performed using the full-width-half-maximum (FWHM) method.…”
Section: Methodsmentioning
confidence: 99%
“…These advances may be channeled into developing objective imaging biomarkers for predicting COVID-19 outcomes. Using appropriate density threshold ranges, it is possible to differentiate lung parenchyma involved in COVID-19 from normal lung parenchyma ( 18 ).…”
Section: Introductionmentioning
confidence: 99%